Understanding growth and poverty : theory, policy, and empirics - Nallari, Raj, 1955-; Griffith, Breda; World Bank. (Washington DC: World Bank, 2011)
"The Overstory is a novel by Richard Powers published in 2018 by W. W. Norton & Company. It is Powers' twelfth novel. The book is about nine Americans whose unique life experiences with trees bring them together to address the destruction of forests. Powers was inspired to write the work while teaching at Stanford University, after he encountered giant redwood trees for the first time." -- Library Thing
The Complexity of North-South Links -- Monetary Policies and Capital Flows -- North-South Capital Flows -- Globalization, Volatility, and Growth -- The Financial Crisis of 2008 and Global Growth -- Growth Booms -- The Microeconomic Foundations of Growth -- Conclusion -- Notes -- Bibliography -- ch. 20 The Politics of Growth and Poverty -- Political Power and Economic Institutions -- Economic Origins of Political Regimes -- Do Democratic Countries Grow Faster than Dictatorships? -- The Interplay of Politics and Economics -- Conclusion -- Notes -- Bibliography -- ch. 21 Climate Change and the Wealth of Nations -- National Wealth and Genuine Saving -- Consumption Saving, and a Counterfactual to the Hartwick Rule -- How Does Natural Capital Affect Well-Being? -- High Carbon, High Growth -- Mitigation of and Adaptation to Climate Change -- Conclusion -- Annex Empirical Evidence of the Causes of Growth -- Notes -- Bibliography.
Includes bibliographical references and index.
Keywords: Poverty; Economic development; Development economics